Research on sleep disorders and related risk factors among healthcare workers from Fujian province supporting Hubei province during the COVID-19 pandemic - Yongxi, Wu; Zexin, Lin; Yiqi, Lin; Qianwen, Lin; Xiaoliang, Xie; Shichao, Wei (Frontiers in Psychology, 2024)
Objective To explore the impact of COVID-19 on the sleep of healthcare workers from Fujian Province supporting Hubei Province and its related risk factors. Methods A cross-sectional, anonymous, self-reported online questionnaire survey was conducted among all participants. The questionnaire consisted of five parts: sociodemographic characteristics and COVID-19 epidemic-related factors, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Morningness-Eveningness Questionnaire-5 (MEQ-5), and 12-item General Health Questionnaire (GHQ-12). Results Among 552 participants, 203 (36.8%) had a PSQI score > 7, indicating the presence of sleep disorders. Logistic regression analysis revealed that sleep disorders were independently associated with a history of previously diagnosed sleep disorders (OR 6.074, 95% CI 2.626–14.049, P < 0.001), rotating night shifts > 3 times per week (OR 3.089, 95% CI 1.650–5.781, P < 0.001), using electronic devices before sleep >1 h (OR 1.685, 95% CI 1.131–2.511, P = 0.010), concern about contracting COVID-19 (OR 1.116, 95% CI 1.034–1.204, P = 0.005), perception of societal support for supporting healthcare workers in Hubei (OR 0.861,95% CI 0.744–0.998, P = 0.047) (OR 0.861, 95% CI 0.744–0.998, P = 0.047), non-medical staff (OR 0.257, 95% CI 0.067–0.987, P = 0.048), ESS score (OR 1.068, 95% CI 1.018–1.121, P = 0.007), and GHQ-12 score (OR 1.511, 95% CI 1.281–1.782, P < 0.001). Conclusion Sleep disorders were highly prevalent among healthcare workers from Fujian Province supporting Hubei Province during the COVID-19 pandemic. Risk factors for sleep disorders included a history of previously diagnosed sleep disorders, rotating night shifts > 3 times per week, using electronic devices before sleep >1 h, excessive concern about contracting COVID-19, and poorer psychological health. Higher perceived societal support and understanding of support for healthcare workers supporting Hubei were associated with a reduced risk of sleep disorders, as was being non-medical staff. Providing more sleep hygiene education and psychological health services for frontline healthcare workers is necessary.